The effects of cryopreservation on PBMCs transcriptome profile - Li, Xuan; Chen, Qian; Higgins, Jeanette; Cook, Kyndal; Baseler, Michael W.; Imamichi, Tomozumi; Chang, Weizhong (Frontiers in Immunology, 2025)
Cryopreservation is a key method for long-term storage of biological specimens. The development of optimal cryopreservation and recovery conditions will minimize storage-related damage. The effect of the cryopreservation and recovery condition we used on peripheral blood mononuclear cells (PBMCs) has previously been evaluated using microarray analysis. The emerging single-cell RNA sequencing (scRNA-seq) technology enables deeper exploration of cellular heterogeneity and function. In the current study, we further optimized the cryopreservation and recovery procedure based on cell viability of PBMC cryopreserved for one-year evaluated using trypan blue staining and propidium iodide (PI) staining with FACS. The procedure was further validated by scRNA-seq using PBMC cryopreserved for two different lengths of time: six and 12 months, in comparison with fresh cells. We identified six major immune cell types from both fresh and recovered cryopreserved PBMCs, including monocytes, dendritic cells (DCs), natural killer (NK) cells, CD4+ T cells, CD8+ T cells, and B cells. The cell viability of all identified immune cell types was relatively stable after both six and 12 months of cryopreservation; however, the number of cells sequenced in the scRNA-seq data declined significantly by 32% after 12 months of cryopreservation, suggesting reduced scRNA-seq cell capture efficiency. Furthermore, the transcriptome profiles of cryopreserved samples did not show substantial perturbation over the 12-month testing period, although a few key genes involved in AP-1 complex, stress response or response to calcium ion exhibited significant change, but with very small scale (< two folds). In conclusion, even though we observed a reduction of scRNA-seq cell capture efficiency after 12-month cryopreservation, our results demonstrated that the optimized cryopreservation and recovery procedure has minimal effect on PBMC viability, population composition and transcriptomic profiles after 6 or 12 months of storage.